2006
DOI: 10.1016/j.freeradbiomed.2006.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic hyperoxia reduces hippocampal pyruvate dehydrogenase activity

Abstract: The pyruvate dehydrogenase complex (PDHC) is a mitochondrial matrix enzyme that catalyzes the oxidative decarboxylation of pyruvate and represents the sole bridge between anaerobic and aerobic cerebral energy metabolism. Previous studies demonstrating loss of PDHC enzyme activity and immunoreactivity during reperfusion after cerebral ischemia suggest that oxidative modifications are involved. This study tested the hypothesis that hyperoxic reperfusion exacerbates loss of PDHC enzyme activity, possibly due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 76 publications
2
67
0
Order By: Relevance
“…22 In the current study, there was no change in enrichment or 13 Clactate labeling in the cortex, providing further evidence that hippocampal metabolism is particularly vulnerable in this clinically relevant model of global ischemia/reperfusion. The recent report by Richards et al 3 that there was no change in PDHC activity in the cortex, regardless of the reperfusion paradigm, is consistent with this concept.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…22 In the current study, there was no change in enrichment or 13 Clactate labeling in the cortex, providing further evidence that hippocampal metabolism is particularly vulnerable in this clinically relevant model of global ischemia/reperfusion. The recent report by Richards et al 3 that there was no change in PDHC activity in the cortex, regardless of the reperfusion paradigm, is consistent with this concept.…”
Section: Discussionsupporting
confidence: 56%
“…2,3,6,[17][18][19][20] In particular, previous results from our laboratory showed a 33% decrease in total hippocampal PDHC activity after hyperoxic reperfusion compared with nonischemic control animals. 3 Cardell et al 19 reported a 50% reduction Amino acids were determined by HPLC on extracts of frozen hippocampi from sham-operated, nonischemic animals and from animals after 10 minutes of cardiac arrest and 2-hour reperfusion using hyperoxic or normoxic resuscitation (Methods). Values are meanϮSE for nϭ7 nonischemic, 7 hyperoxic, and 6 normoxic animals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Several studies have demonstrated that when animals are hyperoxic during reperfusion following global cerebral ischemia, brain tissue oxidative stress markers, impaired cerebral energy metabolism, neuronal death, and neurologic impairment are greater than what is observed following normoxic reperfusion (Balan et al, 2006;Liu et al, 1998;Mickel et al, 1987;Richards et al, 2006;Vereczki et al, 2006). These findings have led to the concept that brain tissue oxygenation in excess of what is necessary to saturate metabolic O 2 utilization is toxic during early reperfusion, when altered intracellular conditions, e.g., pH, [Ca 2+ ], etc., may either promote the formation of reactive oxygen species (ROS) or inhibit their detoxification (Rosenthal and Fiskum, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The most acute influence of ROS/RNS on mitochondria is mediated by oxidative modifications of proteins present in the electron transport chain (ETC) [1,2], other metabolic proteins, e.g., pyruvate dehydrogenase aconitase and α-ketogluatarate dehydrogenase [3][4][5], and the inner membrane permeability transition pore (PTP) [6,7]. Oxidation of cardiolipin, a phospholipid primarily lo-…”
Section: Abstract Oxidative Stress and Loss Of Cellular Camentioning
confidence: 99%